The Role Of Job Stress In Mediating The Effect Of Hard Skills, Soft Skills, And Digitalization On Employee Job Readiness - Isma Putri Utami; Yohanes Susanto; Herman Paleni; Dheo Rimbano (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of hard skills, soft skills, and digitalization on employee job readiness and the mediating role of job stress at PT Bank Mandiri (Persero) Tbk Lubuklinggau Branch. The method used is quantitative with a survey approach. The results showed that hard skills, soft skills, and digitalization partially affected work readiness. Simultaneously, the three variables also have a considerable impact, indicating that work readiness is influenced by various skills that support each other. In addition, job stress is proven to act as an intervening variable in the relationship between hard and soft skills and job readiness. Thus, developing technical, interpersonal, and digital skills needs to be accompanied by effective stress management to improve work readiness optimally. These findings provide important implications for human resource management in the banking sector, particularly in enhancing employee competencies and work readiness in the digital era.